ANALISIS TEORI ANTRIAN DENGAN MULTI CHANNEL (M/M/c) PADA STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) (Studi Pada SPBU Soekarno Hatta MALANG) (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT Queuing is a phenomenon faced by customers in the service industry. One of them happened at the Soekarno Hatta gas station where customer accumulation often occurs every morning and evening. This study aims to analyze the queue that occurs and determine the optimal number of servers. Data collection is done by observing and recording the queues that occur during rush hour in the morning and evening. The queue system configuration that is applied by the Soekarno Hatta gas station can be stated in notation (M / M / c). The service discipline applied to the Soekarno Hatta gas station is the discipline of First In First Out (FIFO) services.From the results of the queuing system performance calculation at Soekarno Hatta gas station, when using 3 servers there will be a reduction in the average number of times needed by customers in the queue of 86.92%. This statement was strengthened by the increase in the server idle rate of 3.47%. The total cost per customer uses 2 server services is Rp.26,437 and if using 3 servers is Rp. 30,919. The electricity operating costs for 2 Servers are Rp. 1,398 per hour while for 3 Servers is Rp. 1,092 per hour. Based on research conducted by the Soekarno Hatta gas station, it is better to operate 3 servers than 2 servers or 4 servers. Keywords: Customers, Servers, Multi Channel Queues, Soekarno Hatta gas stations.